2022
DOI: 10.1039/d2cc01363k
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt and iron phosphates with modulated compositions and phases as efficient electrocatalysts for alkaline seawater oxidation

Abstract: Electrocatalyst serving for both fresh water and real seawater electrolysis is very limited. In this work, we have developed series of iron-tuned cobalt phosphates and cobalt-tuned iron phosphate solid solutions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Further, the role of composition and structure of metal phosphates showed a significant role toward enhanced OER activity in alkaline seawater, as recently explored by our group. 12 A series of CoFe-phosphates were developed by tuning the composition as well as the phases, which showed interesting phase transformation from Co 3 (PO 4 ) 2 to Fe 2 (PO 4 )O and Fe 4 (PO 4 ) 3 (OH) 3 with variable quantity upon increasing the Fe-content. We found that with Fe-incorporation in trace amounts, the electrocatalyst exhibited outstanding activity, reaching 500 mA cm −2 current density at 1.55 V vs. RHE, well below the limiting cell voltage for OER (1.72 V), even in highly chloride-containing (1 M NaCl) alkaline electrolyte.…”
Section: Challenges and Tackling Of Seawater Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the role of composition and structure of metal phosphates showed a significant role toward enhanced OER activity in alkaline seawater, as recently explored by our group. 12 A series of CoFe-phosphates were developed by tuning the composition as well as the phases, which showed interesting phase transformation from Co 3 (PO 4 ) 2 to Fe 2 (PO 4 )O and Fe 4 (PO 4 ) 3 (OH) 3 with variable quantity upon increasing the Fe-content. We found that with Fe-incorporation in trace amounts, the electrocatalyst exhibited outstanding activity, reaching 500 mA cm −2 current density at 1.55 V vs. RHE, well below the limiting cell voltage for OER (1.72 V), even in highly chloride-containing (1 M NaCl) alkaline electrolyte.…”
Section: Challenges and Tackling Of Seawater Oxidationmentioning
confidence: 99%
“…10,11 Therefore, to overcome these existing obstacles, various strategies have been identified that involve the rational designing of the robust electrocatalyst, which can withstand the corrosive environment of the seawater along with an impressive performance. 12,13 In fact, nowadays, another evolving strategy such as electrolyte engineering by adding special additives into seawater is grabbing much attention due to their ability in protecting electrodes from corrosive CER/BER reactions. 14 Further, the existence of various dissolved ions such as Ca 2+ and Mg 2+ , along with other small particulates such as bacteria and microbes, can additionally hinder the seawater electrolysis process by electrode poisoning, especially at the cathode, thereby blocking the electroactive sites, impairing the durability of the electrocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that the activity of OER catalysts degrades rapidly in the seawater electrolyte due to the corrosive effects of chloride ions (Cl – ) on the catalytic electrode. , Additionally, the chloride ion concentration rises proportionally as seawater is consumed during the OER process. This increase in chloride ions can obstruct the active sites of the catalyst and reduce the number of water molecules or hydroxide ions on the catalyst surface, thereby leading to a decline in catalytic performance. As such, maintaining high catalytic activity and stability during direct seawater electrolysis proves challenging. , Hence, the development of a catalyst that demonstrates both high activity and stability in high-salinity seawater is of paramount importance for the successful realization of large-scale seawater splitting processes.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, a high overpotential is usually required to achieve a large current density, in which case the oxidation of Cl À to form undesired ClO À will compete with the anodic oxygen evolution reaction (OER), decreasing the electrolysis efficiency of seawater. 12,13 In addition to Cl À oxidation, the microorganisms, charged ions, and small particulates in seawater may cause electrocatalyst performance and durability degradation. 14 Accordingly, seeking robust and high-activity catalysts capable of electrolyzing alkaline seawater has become a goal.…”
mentioning
confidence: 99%